Heart Rate Variability and Recurrent Stroke and Myocardial Infarction in Patients With Acute Mild to Moderate Stroke - von Rennenberg, Regina; Krause, Thomas; Herm, Juliane; Hellwig, Simon; Scheitz, Jan F.; Endres, Matthias; Haeusler, Karl Georg; Nolte, Christian H. (Frontiers in Neurology, 2021)
Objectives In patients with acute ischemic stroke, reduced heart rate variability (HRV) may indicate poor outcome. We tested whether HRV in the acute phase of stroke is associated with higher rates of mortality, recurrent stroke, myocardial infarction (MI) or functional outcome. Materials and Methods Patients with acute mild to moderate ischemic stroke without known atrial fibrillation were prospectively enrolled to the investigator-initiated Heart and Brain interfaces in Acute Ischemic Stroke (HEBRAS) study (NCT 02142413). HRV parameters were assessed during the in-hospital stay using a ten-minute section of each patient’s ECG recording at day- and nighttime, calculating time and frequency domain HRV parameters. Frequency of a combined endpoint of recurrent stroke, MI or death of any cause and the respective individual events were assessed twelve months after the index stroke. Patients’ functional outcome was measured by the modified Rankin Scale (mRS) at twelve months. Results We included 308 patients (37% female, median NIHSS=2 on admission, median age 69 years). Complete follow-up was achieved in 286/308 (93%) patients. At twelve months, 32 (9.5%), 5 (1.7%) and 13 (3.7%) patients had suffered a recurrent stroke, MI or death, respectively. After adjustment for age, sex, stroke severity and vascular risk factors, there was no significant association between HRV and recurrent stroke, MI, death or the combined endpoint. We did not find a significant impact of HRV on a mRS ≥ 2 twelve months after the index stroke. Conclusion HRV did not predict recurrent vascular events in patients with acute mild to moderate ischemic stroke.